2006
DOI: 10.1111/j.2006.0030-1299.15116.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of productivity on species–area curves in herbaceous vegetation: evidence from experimental and observational data

Abstract: The effects of productivity on the parameters of the species–area curve were investigated in this paper using two data sets on terrestrial plant communities: (1) one including 48 plots in 12 experimental sites on ploughed, formerly cultivated fields in the Siena region, Italy, and (2) one including 40 plots in hay meadows in the Bremen region, Germany. In both regions, species presence of vascular plants was recorded in nested plots ranging in size from 0.004 to 256 m2 and 0.001 to 1000 m2, respectively. Produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 31 publications
2
39
0
1
Order By: Relevance
“…Here, a populous regional species pool of more than 80 species was associated with local species densities of 10 species m Ϫ2 or less; again, local richness was more heavily regulated by competitive exclusion. Given such evidence, it is not surprising that a study conducted in two regions of Europe (Siena, Italy, and Bremen, Germany; Chiarucci et al 2006) found poor correlation between regional species pool size and local species richness.…”
Section: The Role Of Local-scale Processes In Regulating Large-scale mentioning
confidence: 99%
“…Here, a populous regional species pool of more than 80 species was associated with local species densities of 10 species m Ϫ2 or less; again, local richness was more heavily regulated by competitive exclusion. Given such evidence, it is not surprising that a study conducted in two regions of Europe (Siena, Italy, and Bremen, Germany; Chiarucci et al 2006) found poor correlation between regional species pool size and local species richness.…”
Section: The Role Of Local-scale Processes In Regulating Large-scale mentioning
confidence: 99%
“…The SAR was tested using two models: the commonly used log-log power function, S = c A Z (Arrhenius 1921;Tjørve 2003), and a curved model called the quadratic power function, S = 10 (b0?b1 logA?b2 (logA)2) (Chiarucci et al 2006), where S = species number, A = area, z = the slope (z value) and c and b x are constants. The models were chosen to fit our empirical data and according to Dengler (2009) both models generally perform well.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with island biogeography theory (MacArthur and Wilson 1967) and previous SAR studies including beetles (e.g., Lövei et al 2006;Magura et al 2001;Vries de et al 1996). The SAR model that best explained the relationship was the quadratic power function (Chiarucci et al 2006;Dengler 2009), where the fitted SA-curve shows a rapid initial increase in the number of sand species followed by a peak at around 2.5-3 ha and then a decrease (Fig. 3).…”
Section: Species-area Relationshipsmentioning
confidence: 99%
“…Alpine pastures on the Plateau are traditionally grazed by yaks and/or sheep and are managed by single or multiple families (Cao et al 2011;Cao et al 2013). Livestock grazing can affect plant species composition, which influences the form and parameters of SAR in many habitats (Hiernaux 1998;de Bello et al 2007;Chen et al 2008). However, there is lack of available information on the selective grazing behaviors of domestic yaks and sheep on the Northern Tibetan Plateau.…”
Section: Study Areamentioning
confidence: 99%
“…Therefore, the two theories are not necessarily mutually exclusive, and stochastic processes, environmental filters (temperature, precipitation, moisture and nutrients in soils), and biotic interactions may simultaneously govern local species richness and composition (Lortie et al 2004). For example, Chiarucci et al (2006) suggested that the intercepts and slopes of SAR curves were dependent on habitat types and plant community properties. In our results, we found that both the slopes and intercepts of the SAR curves for all species and forbs were significantly higher in alpine meadows than in alpine steppes ( Figure 3 and Table 2).…”
Section: Tablementioning
confidence: 99%